Thermal characterization and design of GaAs HBT with heat source drifting effects under large current operating condition. (June 2020) - Sun, Xiaohong; Zhang, Xiaodong; Sun, Yunfei
Abstract: A detailed investigation on internal thermal phenomena of GaAs hetero bipolar transistor (HBT) structure is presented especially when sub-collector is considered. This allows for a realistic and physical electro-thermal analysis. With the help of Joule heating calculation, a drifting heat source across the collector region is observed under real operation of large current density. Temperature distribution also verifies this phenomenon with further simulation. To get a better insight into the mechanism of the drifting action, the associated distributed high electric field is then analyzed. A thermally optimized HBT is then proposed with Gaussian doping in the sub-collector region. Compared to the original structure, the new design shows a reduction of maximum temperature by 9.5% with base current density of 2e-5 A/μm. The findings in this paper can help with accurate thermal modeling and provide suggestions for thermal optimized HBT design as well.